2014
DOI: 10.3801/iafss.fss.11-234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sample Width and Sidewalls on Downward Flame Spread over XPS Slabs

Abstract: To study the effects of sample width and sidewalls on downward flame spread over extruded polystyrene (XPS) slabs, a series of laboratory-scale experiments were conducted. Flame shape, flame spread rate, mass loss rate and temperature were recorded. For XPS without sidewalls, the average maximum flame height (H) and average flame area per unit of width (A/w) rise linearly with an increase in sample width (w) and mass loss rate per unit of width. When sidewalls are absent, flame spread rate first drops and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…Equation m l = m a /L indicates a positive correlation between the average mass loss rate per unit length and the characteristic length. The same conclusion in the XPS sandwich panel in high-rise building fire spreading was also produced [31]. It was deduced that m l rose with an increase in the sample length.…”
Section: Mass-loss Rate Of the Metal Sandwich Panelsupporting
confidence: 62%
“…Equation m l = m a /L indicates a positive correlation between the average mass loss rate per unit length and the characteristic length. The same conclusion in the XPS sandwich panel in high-rise building fire spreading was also produced [31]. It was deduced that m l rose with an increase in the sample length.…”
Section: Mass-loss Rate Of the Metal Sandwich Panelsupporting
confidence: 62%
“…Because the air enrolling in the X direction is mainly concentrated in the front [7,16], and the influence of the back plane on the air enrolling is mainly reflected near the back plane. Therefore, this paper only analyzes the change of air velocity in Y and Z directions near the backboard.…”
Section: Influence Of Backboard On Flow Field and Air Entrainmentmentioning
confidence: 99%
“…Carmignani et al [6] studied the two-dimensional downward fire propagation of PMMA plate (side limited, no backboard), and the results showed that the pyrolysis front was linear. An et al [7], Luo et al [8], Yan et al [9] experimentally studied the effect of U-shaped structure (side limited with backboard) on the downward spreading of expanded polystyrene (XPS) and PMMA plates, respectively. The results showed that, under the U-shaped structure, the temperature of XPS and PMMA plates decreased significantly.…”
Section: Introductionmentioning
confidence: 99%